Gambaran Fungsi Kognitif Pada Lansia Di Desa Rapa Laok Kecamatan Omben Kabupaten Sampang - Dalilah Dalilah (Fakultas Ilmu Kesehatan, 2019)
Mental disorders that are often found in the elderly are depression and cognitive impairment. Research on the ability of cognitive aspects and memory abilities in the elderly shows that they have less memory and intelligence abilities, despite the controversy, intelligence tests clearly show a decrease in intelligence in the elderly The design of this study was descriptive research, the population in this study were 30 elderly using total sampling. The instrument used in this study was the MMSE (Mini-Mental State Examination) questionnaire. data analysis using descriptive statistical tests. Most of the cognitive functions of the elderly with a bad category are 19 elderly (63.3%) and almost half are in the good category as many as 11 elderly (36.7%). This can be influenced by age factors, considering that the sample used as the elderly in this study was elderly. In the elderly besides decreasing physical function with aging, memory and intelligence decline generally occurs. In addition, from the answers of the elderly on the questionnaire submitted by researchers, most of the elderly experienced difficulties when instructed to spell words and draw. This is most likely influenced by the educational background of the elderly, where it was found that most of the elderly with the last education status were not in school and elementary school.